The Financial - Market Potential of Croatian Small and Medium-Sized Enterprises in Attracting Venture Capital - Marija Šimić Šarić (Elektronički Zbornik Radova Veleučilišta u Šibeniku, 2024)
An investment-ready entrepreneur is the one who is able to understand the specific preferences of investors and is able to satisfy or respond to these preferences in terms of risk and return, providing an appropriate placement structure and relevant information. Therefore, this research analyzes the financial and market potential of Croatian small and medium-sized enterprises in attracting venture capital. On the basis of existing research, a theoretical model called the financial-market potential of the enterprise was formed. Through multiple log-linear regression, its importance in attracting venture capital was examined from the perspective of entrepreneurs who attracted venture capital. The influence of the rate of return on assets, financing with own capital and quasi-market share on the amount of attracted venture capital is positive, while the influence of the rate of return on equity is negative, so the hypothesis of the existence of a positive influence of the financial-market potential of the enterprise on the amount of attracted venture capital was accepted. The scientific contributions of the conducted research lies in the development of scientific knowledge about the investment criteria of risk capital, the formation of a theoretical model of the financial-market potential of the enterprise, as well as in the empirical verification of the established model. The limitation of the research itself stems from the fact that the venture capital market in Croatia is insufficiently developed and the associated small number of investments. Therefore, the aforementioned research can be extended to the countries of Central and Eastern Europe in the future.